Respuesta :

gmany

[tex]-\dfrac{2}{3}(3x-4)+3x=\dfrac{5}{6}\ \ \ \ |\text{use distributive property}\\\\-\dfrac{2}{\not3_1}\cdot\not3^1x+\dfrac{8}{3}+3x=\dfrac{5}{6}\\\\-2x+3x+\dfrac{8}{3}=\dfrac{5}{6}\ \ \ \ |-\dfrac{8}{3}\\\\x=\dfrac{5}{6}-\dfrac{8}{3}\\\\x=\dfrac{5}{6}-\dfrac{8\cdot2}{3\cdot2}\\\\x=\dfrac{5}{6}-\dfrac{16}{6}\\\\\boxed{x=-\dfrac{11}{6}}[/tex]

Other method:

[tex]-\dfrac{2}{3}(3x-4)+3x=\dfrac{5}{6}\ \ \ \ |\cdot6\\\\2(-2)(3x-4)+18x=5\\\\-4(3x-4)+18x=5\ \ \ \ |\text{use distributive property}\\\\-12x+16+18x=5\ \ \ \ |-16\\\\6x=-11\ \ \ \ |:6\\\\\boxed{x=-\dfrac{11}{6}}[/tex]

Answer:

x=  -11/6

Step-by-step explanation:

I took the test!

ACCESS MORE